Knowledge of Control Methods and their Application in the Practice of Small and Medium Enterprises in the Northern Great Plain Region - Lakatos, Vilmos; Béresné Mártha, Bernadett; Tömöri, Gergő (International Journal of Engineering and Management Sciences, 2020)
Like large companies, the small, and medium-sized businesses need also all the information to ensure the efficiency and effectiveness of their business by making sound management decisions. Compared to large companies, SMEs have significant development potential, which can be created in part by the companies themselves, possibly through the introduction of new-modern management - business administration methods or economic policy measures (= targeted and efficient support system), which, by stimulating R & D & I processes, serves to increase competitiveness and contribute more and proportionally to domestic GDP and exports. The analysis presented in the study covers the controlling knowledge of the leading SMEs of the Northern Great Plain Region, the conscious or unconscious application of controlling tools, the assessment of succession, customer and supplier valuation and certain areas of managerial accounting. Overall, it can be concluded from the small sample size that the use of controlling tools is proportional to the size of the business, but nevertheless, many mid-size business executives do not require the collection and analysis of insider information that could explicitly help decision making for example  through advanced costing procedures.